Identification of Novel NSD1 variations in four Pediatric cases with sotos Syndrome - Zhuo Ren; Ling Yue; Hua-ying Hu; Xiao-lin Hou; Wen-qi Chen; Ya Tan; Zhe Dong; Jing Zhang (BMC, 2024)
Abstract Objective Sotos syndrome (SOTOS) is an uncommon genetic condition that manifests itself with the following distinctive features: prenatal overgrowth, facial abnormalities, and intellectual disability. This disorder is often associated with haploinsufficiency of the nuclear receptor-binding SET domain protein 1 (NSD1)gene. We investigated four pediatric cases characterized by early-onset overgrowth and developmental delay. The primary objective of this study was to achieve accurate genetic diagnoses. Design&Methods A sequential analysis approach comprising chromosomal karyotyping, whole exome sequencing, and microarray analysis was conducted. Results All four cases exhibited variations in the NSD1 gene, with the identification of four previously unreported de novo variants, each specific to one case.Specifically, Case 1 carried the NSD1 (NM_022455): c.2686 C > T(p.Q896X) variant, Case 2 had the NSD1 (NM_022455): c.2858_2859delCT(p.S953X) variant, Case 3 displayed a chromosomal aberration, chr5: 5q35.2q35.3(176,516,604-176,639,249)×1, which encompassed the 5'-untranslated region of NSD1, and Case 4 harbored the NSD1 (NM_022455): c.6397T > G(p.C2133G) variant. Conclusion This study not only provided precise diagnoses for these cases but also supplied significant evidence to facilitate informed consultations. Furthermore, our findings expanded the spectrum of mutations associated with SOTOS.